Factores subjetivo - jurídicos que impiden la aplicación del proceso de terminación anticipada en los procesos penales, en el Primer Juzgado Penal del distrito judicial de Huancavelica, periodo 2010-2011 - Dávila Martínez, Lucinda (2023)
This study aimed to identify and characterize the subjective and legal factors that hindered the implementation of the early termination process in criminal proceedings conducted at the First Criminal Court of the Judicial District of Huancavelica during the period 2010-2011. The sample included 124 participants, comprising prosecutors, judges, victims, defendants, and lawyers involved in criminal proceedings within the district. A survey was conducted in accordance with the provisions of Article 468 of the New Code of Criminal Procedure. The survey's validity was supported by the statistical analysis of the Chi-Square test, yielding a value of 0.372, indicating high reliability. The primary rating scale used for assessing responses was dichotomous, with participants choosing "yes" or "no." The survey results validated the hypothesis proposed in this research study. Through item analysis, it was found that among the questions in the applied surveys, the units of analysis constituting the study sample tended to evaluate the personal and professional behavior of individuals involved in criminal proceedings. The variable of Early Termination Process emerged as a factor facing obstacles, as legal professionals and individuals involved in criminal proceedings demonstrated the influence of the level of conflict culture and the pursuit of profit in fulfilling their professional duties, coupled with a limited or negligible understanding of the spirit of Article 468 of the New Code of Criminal Procedure.